A missed opportunity: birth registration coverage is lagging behind Bacillus Calmette-Guérin (BCG) immunization coverage and maternal health services utilization in low- and lower middle-income countries - M. Hafizur Rahman; Amber Bickford Cox; Samuel L. Mills (BMC, 2019)
Abstract Background Civil registration and vital statistics (CRVS) systems lay the foundation for good governance by increasing the effectiveness and delivery of public services, providing vital statistics for the planning and monitoring of national development, and protecting fundamental human rights. Birth registration provides legal rights and facilitates access to essential public services such as health care and education. However, more than 110 low- and middle-income countries (LMICs) have deficient CRVS systems, and national birth registration rates continue to fall behind childhood immunization rates. Using Demographic and Health Survey (DHS) and Multiple Indicator Cluster Survey (MICS) data in 72 LMICs, the objectives are to (a) explore the status of birth registration, routine childhood immunization, and maternal health services utilization; (b) analyze indicators of birth registration, routine childhood immunization, and maternal health services utilization; and (c) identify missed opportunities for strengthening birth registration systems in countries with strong childhood immunization and maternal health services by measuring the absolute differences between the birth registration rates and these childhood and maternal health service indicators. Methods We constructed a database using DHS and MICS data from 2000 to 2017, containing information on birth registration, immunization coverage, and maternal health service indicators. Seventy-three countries including 34 low-income countries and 38 lower middle-income countries were included in this exploratory analysis. Results Among the 14 countries with disparity between birth registration and BCG vaccination of more than 50%, nine were from sub-Saharan Africa (Tanzania, Uganda, Gambia, Mozambique, Djibouti, Eswatini, Zambia, Democratic Republic of Congo, Ghana), two were from South Asia (Bangladesh, Nepal), one from East Asia and the Pacific (Vanuatu) one from Latin America and the Caribbean (Bolivia), and one from Europe and Central Asia (Moldova). Countries with a 50% or above absolute difference between birth registration and antenatal care coverage include Democratic Republic of Congo, Gambia, Mozambique, Nepal, Tanzania, and Uganda, in low-income countries. Among lower middle-income countries, this includes Eswatini, Ghana, Moldova, Timor-Leste, Vanuatu, and Zambia. Countries with a 50% or above absolute difference between birth registration and facility delivery care coverage include Democratic Republic of Congo, Djibouti, Moldova, and Zambia. Conclusion The gap between birth registration and immunization coverage in low- and lower middle-income countries suggests the potential for leveraging immunization programs to increase birth registration rates. Engaging health providers during the antenatal, delivery, and postpartum periods to increase birth registration may be a useful strategy in countries with access to skilled providers.